2024
DOI: 10.1080/19490976.2023.2298026
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurized Akkermansia muciniphila improves irritable bowel syndrome-like symptoms and related behavioral disorders in mice

Maëva Meynier,
Valentine Daugey,
Geoffroy Mallaret
et al.

Abstract: Gut – brain communications disorders in irritable bowel syndrome (IBS) are associated with intestinal microbiota composition, increased gut permeability, and psychosocial disturbances. Symptoms of IBS are difficult to medicate, and hence much research is being made into alternative approaches. This study assesses the potential of a treatment with pasteurized Akkermansia muciniphila for alleviating IBS-like symptoms in two mouse models of IBS with different etiologies. Two clinically relevant animal models were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…While pasteurization inactivates microorganisms and their production of SCFAs, this process also increases accessibility to extracellular bacterial proteins which resist heat denaturation 42 . Amuc_1100 is an outer membrane protein specific to A. muciniphila which appear to remain stable at pasteurization temperature, and recapitulates the beneficial effect of live or pasteurized A. muciniphila in the context of metabolic disorders and colitis 38,42,[81][82][83][84] . Various studies have shown that purified Amuc_1100* is an efficient activator of the TLR-2 receptor 37,42,85 .…”
Section: Discussionmentioning
confidence: 97%
“…While pasteurization inactivates microorganisms and their production of SCFAs, this process also increases accessibility to extracellular bacterial proteins which resist heat denaturation 42 . Amuc_1100 is an outer membrane protein specific to A. muciniphila which appear to remain stable at pasteurization temperature, and recapitulates the beneficial effect of live or pasteurized A. muciniphila in the context of metabolic disorders and colitis 38,42,[81][82][83][84] . Various studies have shown that purified Amuc_1100* is an efficient activator of the TLR-2 receptor 37,42,85 .…”
Section: Discussionmentioning
confidence: 97%
“…In one study in mouse models (C57BL6/J mice subjected to neonatal maternal separation and Citrobacter rodentinum infection), supplemented with pasteurised A. muciniphila was shown to reduce visceral hypersensitivity by affecting intestinal barrier function. In addition, a reduction in anxiety-like behaviour, as well as memory impairment and an effect on pain sensations, has been shown [38].…”
Section: Gut Diseasesmentioning
confidence: 99%
“…In addition to the use of A. muciniphila in the treatment of IBD, the use of postbiotic supplementation (pasteurized A. muciniphila ) in irritable bowel syndrome (IBS)-like symptoms has recently received attention. Meynier et al [ 59 ] aimed to investigate the effects of pasteurized Akkermansia muciniphila on alleviating IBS-like symptoms and related behavioral disorders in mice. The researchers used two mouse models to mimic IBS symptoms: (i) a non-inflammatory model to induce colonic hypersensitivity (NMS), and (ii) a Citrobacter rodentium post-infectious IBS (PI-IBS) model.…”
Section: Gut Diseasesmentioning
confidence: 99%
“…Moreover, the study revealed improvement in anxiety-like behavior and memory defects and neuroinhibitory effects with reduced anxiety and enhanced cognitive function in the PI-IBS model treated with pasteurized A. muciniphila. Of interest, the treatment did not significantly alter the overall composition of the fecal microbiota, indicating that its beneficial effects might be due to direct interactions with the host rather than altering microbiota composition [ 59 ].…”
Section: Gut Diseasesmentioning
confidence: 99%